Straw yield optimization strategy for rice (Oryza sp L. var Nerica L14) regrowth under strictly rainfed conditions : impact on mineral content. (2022) - Lucien, Gogbeu Dan Gbongué; François, Konan Yao Kouakou; Dadé, Amari Ler-N'ogn
No abstract available